A randomized study to compare the efficacy and side effects of misoprostol given either orally or vaginally for first trimester medical termination of pregnancy - Tripathi, Urmila; Garg, Pratibha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Medical abortion represents an alternative to first trimester aspiration abortion and has been used by millions of women throughout the world. A numerous study has demonstrated that combination of mifepristone and misporostol is highly efficacious with success rate of approximately 97%. Methods: In the present randomized study 100 women who were requesting for first trimester medical abortion were included in the study. This randomized study was conducted for a period of one year in a tertiary health care centre. All these women were randomly assigned to receive either oral misoprostol (n=52) (group 1) or vaginal misoprostol (n=48) (group 2). We found that after the administration of mifepristone, vaginal misoprostol for the induction of abortion upto 49 days was more effective than oral misoprostol. Results: In present study maximum number of patients were in the age group of 26-30 years. Multiparous women comprised of maximum number of patients in both 70% in group 1 and 83% in group 2. The gestational age at the time of inclusion in study was maximum upto 7 weeks or 49 days gestation in both groups. Acceptability of medical abortion is more in urban locality i.e. 73% in group 1 and 81% in group 2. 73% in group 1 and 79% in group 2 chose to have misoprostol at home. 92% patients in group 1 and 95% patients in group 2 initiated bleeding per vaginum within 4 hours. Side effects like nausea, vomiting and diarrhea were compared. 92.4% patients in group 1 and 97% patients in group 2 who had expulsion of conception without need of surgical intervention was comparable. Only 2 patients in group 1 had incomplete abortion and needed surgical aspiration. Conclusions: This study showed UA-S/D ratio and UA-RI>2SD are significant predictors of perinatal deaths and immediate neonatal resuscitation in preeclampsia. Acute fetal distress in labour or neonatal nursery admission could not be predicted.